Toward Inclusive Education in Medicine - Pardaeva Uguloy Jamolovna; Makhmanazarov Agzam clinic resident (European Journal of Life Safety and Stability (2660-9630), 2024)
Inclusive education in medicine aims to ensure equal access to the educational process for all students, including persons with disabilities. This article considers the main aspects of inclusion in medical education, analyzes the legislative norms regulating this direction, and distinguishes different types of inclusion depending on medical indications. Uzbekistan, as a developing country according to its own model, pays great attention to the educational development of young people. One of these directions in Uzbekistan with the UNICEF organization has introduced several programs to introduce inclusive education for young people with disabilities, which not only improves the quality of life of these children, but also gives them the opportunity to be full-fledged people for society.